KEBIASAAN CUCI TANGAN, KONDISI FASILITAS CUCI TANGAN DAN KEBERADAAN E. COLI PADA TANGAN PENJAMAH MAKANAN DI RUMAH MAKAN DALAM WILAYAH KERJA PUSKESMAS OEBOBO KUPANG TAHUN 2012 - KUSMIYATI KUSMIYATI; ENNI ROSIDA SINAGA; WANTI WANTI (JURNAL INFO KESEHATAN, 2013)
Food is needed for our body as energy source. Food also as source of food borne diseases if it is untreatment well. Here, food handler is important to keep the food higyene. This research aim is to describe the hand washing habit, hand washing facility and the present of E. coli at the food handler’s hands in Oebobo Primary Health Center. This discriptive research use cros sectional study with 50 restorants as samples, and 50 food handler, also 50 hand washing facility as unit sample. This research find only 30% food handler washed their hands more than 10 time a day, and almost always using soap when they did it. Many food handlers wash their hands incorrectly. Many restorant just have 1 hand washing facility, 62% the location separate between staf and consumen, only 58% with run water. This research also find there is E. coli at 16% food handlers’s hand.